2023
DOI: 10.3164/jcbn.22-143
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between body mass index and constipation, gastroesophageal reflux disease, stool forms based on the Bristol Stool Form Scale, and education level: results from an internet survey in Japan

Abstract: Detailed evaluations of body mass index (BMI) and stool form based on the Bristol Stool Form Scale (BSFS) in individuals with constipation, gastroesophageal reflux disease (GERD), and concomitant constipation and GERD have not been performed in Japan. This study was an internet survey conducted to examine the relationships between BMI and constipation, GERD, stool forms based on the BSFS, and education level. This internet-based survey recruited participants from general public survey panels. 10,000 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(81 reference statements)
1
1
0
Order By: Relevance
“…We analyzed the relationships between OBS components and diarrhea and constipation and found that BMI was positively correlated with diarrhea and negatively correlated with constipation. This finding is consistent with previous research results [ 68 , 69 ]. Taking Ogasawara N's study as an example, the author studied the relationship between BMI and BSFS score and found that BMI increased from the BSFS-1/2 through the BSFS-3/4/5 and then the BSFS-6/7 groups in both males and females.…”
Section: Discussionsupporting
confidence: 94%
“…We analyzed the relationships between OBS components and diarrhea and constipation and found that BMI was positively correlated with diarrhea and negatively correlated with constipation. This finding is consistent with previous research results [ 68 , 69 ]. Taking Ogasawara N's study as an example, the author studied the relationship between BMI and BSFS score and found that BMI increased from the BSFS-1/2 through the BSFS-3/4/5 and then the BSFS-6/7 groups in both males and females.…”
Section: Discussionsupporting
confidence: 94%
“… 72 Recent study showed that BMI was inversely related to constipation. 73 This signifies that abnormal body weight in both ends may be related to the constipation prevalence. However, we did not find a significant association between BMI and abnormal weight in relation to constipation, although children with abnormal body weight had a higher constipation prevalence than those without (18.4% vs. 12.9%).…”
Section: Discussionmentioning
confidence: 97%